CLINICAL PRESENTATION OF RENAL CELL CARCINOMA - Rehman, Rana Ataur; Ashraf, Shahzad; Rahim, Jamshed; Hussain, Nadir; Jamil, Muhammad Nasir; Tahir, Muhammad Muzammil (Journal of Ayub Medical College Abbottabad, 2015)
Background: Most common malignant tumour of the kidney is Renal Cell Carcinoma (RCC) and is known for its unpredictable clinical behaviour. Aetiology and risk factors are not completely understood. Extensive workup is being done in the understanding of the disease, especially to diagnose early and to treat promptly. The objective of this study was to determine the clinical presentation and pathological pattern of RCC. Methods: After approval from ethical committee a retrospective review of records was conducted extending from January 2012 to January 2014 to identify clinical characteristics of renal cell carcinomas. The study included all renal cancer patients presented to Sheikh Zayed Hospital Lahore with in this specified period. The data was retrieved regarding, history, physical examination and necessary investigations such as ultrasonsgraphy of abdomen and pelvis and CT scan of abdomen and pelvis. Results: There were total of 50 cases. The male to female ratio was 3:2. Mean age of patients were 52.38 (18-93) years old. Most common clinical presentation was gross haematuria(66%).The mean tumour size was 8.34 (3-24) cm. Tumour histology were clear cell (84%), papillary transitional cell carcinoma (12%) and oncosytoma contributed 4%. Conclusion: We observed that large number of the patients with RCC presented with haematuria and most of them were male. Common pathological type was clear cell carcinoma. Keywords: Renal cell carcinoma, Clinical presentation, Gross haematuria